What if? Integrating scenarios and fiction in food systems policy and governance - Zhou, Yewang; Razzaq, Amar (Frontiers in Sustainable Food Systems, 2025)
Modern food systems face unprecedented challenges that require transformative policy responses beyond conventional forecasting. We argue that scenario building and science fiction narratives can serve as tools for policy innovation, helping stakeholders to consider complexity, weigh trade-offs, and shape more adaptive strategies. By synthesizing insights from foresight studies, participatory scenario exercises, and narrative approaches, this perspective suggests that creative future visions can support new policy pathways toward sustainable food systems. These methods offer co-created visions of possible futures encompassing climate, diets, technologies, and governance systems.